Friday

August 22, 2014

August 22, 2014

Posted by **Amelia** on Saturday, November 21, 2009 at 8:26am.

for integrate e^(bx) cos x

i get

= cos x e^bx/b - int -sin x e^bx/b

= cos x e^bx/b - -sin x e^bx/b^2 - int - cos x e^bx/b^2

this is where i get stuck please help

- Maths -
**bobpursley**, Saturday, November 21, 2009 at 9:05amInt Udv= uv -int vdu

let dv=cosx v=sinx

U=e^bx du=be^bx

int e^bx*cosx=e^bx(sinx)-int(bsinx*e^bx

now, to handel the last term, let

dv=sinx v=-cosx

u=e^bx du=be^bx

int e^bx coxx=e^bx sinx-b[-e^bx cosx -int(-cosx be^bx)

int e^bx cosx=e^bx sinx+be^bx cos x+b^2e^bx cosx

gathering terms,

(1-b^2)__int e^bx cosx__=e^bx(sinx+bcosx)

and you can solve for your original integral underlined. CHECK MY WORK

**Related Questions**

calculus - Find complete length of curve r=a sin^3(theta/3). I have gone thus- (...

TRIG! - Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6...

tigonometry - expres the following as sums and differences of sines or cosines ...

Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...

algebra - Can someone please help me do this problem? That would be great! ...

trig - Reduce the following to the sine or cosine of one angle: (i) sin145*cos75...

Math - Calculus - The identity below is significant because it relates 3 ...

calculus - Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x...

Calc. - Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x ln...

pre-cal - Simplify the given expression........? (2sin2x)(cos6x) sin 2x and cos ...